Oliver Vickery address - Vickery, Oliver
Typescript of an address entitled, "Free Trade and Spiritual Fusion," delivered by Vickery at the International Economic Conference in Moscow, Russia, April 3-10, 1952. Includes biographical sketch of Vickery.
International financier. Born 1903.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Economics -- Congresses; Free trade; Financiers